Social policy and social justice : the IPPR reader (Cambridge, UK : Polity Press, 1998)
New frameworks for the twenty-first century. Issues and debates in social policy. Service design and delivery.
Keywords: Great Britain; Social policy; Social justice; Social justice -- Great Britain; Great Britain -- Social policy -- 1979-